{[ promptMessage ]}

Bookmark it

{[ promptMessage ]}

weak acid-weak base salt pH (1)

weak acid-weak base salt pH (1) - (NH 4 pK A(HX The pH of...

This preview shows page 1. Sign up to view the full content.

For the reaction NH 4 + + X - == NH 3 + HX (HX is a weak acid and X - a weak base), K eq = [NH 3 ] [HX ] x [H + ] = K A (NH 4 + ) [NH 4 + ] [X - ] [H + ] K A (HX) [NH 3 ] = [HX], and [NH 4 + ] = [X - ], so K eq = [HX] 2 [X - ] 2 Rearranging the K A expression for K A (HX) gives [HX] = [H + ] __ [X - ] K A (HX) K eq = [H + ] 2 ___ K A 2 (HX) [H + ] 2 = K eq K A 2 (HX) = K A (NH 4 + ) K A (HX) 2 pH = pK
This is the end of the preview. Sign up to access the rest of the document.

Unformatted text preview: (NH 4 + ) + pK A (HX) The pH of the solution is the average of the two pK A s, independent of concentration. For ammonium acetate the pK A s are 4.75 and 9.25, and the pH of an ammonium acetate solution is 7.0....
View Full Document

{[ snackBarMessage ]}

Ask a homework question - tutors are online